Analysis of the Implementation of Interactive Flat Panel in Supporting the Digitalization of Learning at SDN 1 Sido Makmur - Anggraini (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
The advancement of technology in the fourth industrial revolution era has made learning digitalization an urgent priority in primary schools, yet infrastructure limitations remain a significant challenge. SDN 1 Sido Makmur received a single 75-inch Interactive Flat Panel (IFP) unit as a government grant under the national school digitalization program. This study aimed to obtain an in-depth understanding of the IFP implementation process, its supporting and inhibiting factors, and its contribution to learning digitalization at SDN 1 Sido Makmur. A descriptive qualitative approach with a case study design was employed. Subjects were determined through purposive sampling, comprising the school principal, three classroom teachers, and six students. Data were collected through observation, semi-structured interviews, and documentation, then analyzed using the Miles, Huberman, and Saldaña interactive model and validated through triangulation. The findings revealed that the single IFP limitation was addressed through a structured rotation schedule, ensuring equitable classroom access and organically fostering a teacher material-sharing community. Planned IFP use increased student motivation, material visualization quality, and active participation, particularly in IPAS and Mathematics. Implementation success was driven more by transformational leadership and teacher collaboration culture than by device quantity. Government IFP programs will have greater impact when accompanied by management guidance and continuous TPACK training.